Kemampuan Berfikir Kreatif Siswa dalam Memecahkan Masalah Matematika Konteks Jembatan Gantung Lahat - M. Arrasikh Hidayatullah Arrasikh; Zulkardi; Ely Susanti (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2022)
This study aims to determine the level of creative thinking of MTs Negeri 1 Muara Enim stnudents in solving mathematical problems in the context of suspension bridges. Taking the subject using purposive sampling technique, the subjects of this study were 3 students with high mathematical abilities. Test questions to see creative thinking skills and interview clues are used as research instruments. Data reduction, data presentation, and drawing conclusions are outlined guidelines in analyzing data in this study. The results showed that the three subjects in this study had been able to demonstrate and present their creative thinking abilities with diverse levels of creative thinking. Based on the results of the answers to the 2 essay questions given, MSE subjects were able to meet the existence of fluency and novelty indicators which showed that they were at the level of creative thinking ability 3 (creative) while CR and RA subjects were only able to meet the novelty indicators that were at the level of creative thinking ability level 2 (quite creative). Keyword: Creative thinking, mathematical problems, bridge contexts